Young Muslim women's political participation in Scotland: Exploring the intersections of gender, religion, class and place. (October 2019) - Finlay, Robin; Hopkins, Peter
Abstract: In this paper, we take an intersectional approach, and examine how gender, religion, class and place intersect and shape the political participations of young Muslim women in Scotland. In particular, we demonstrate how gendered Islamophobia, class status and the political geographies of Scotland are central factors for shaping political identities and political participations. First, we show that although our participants experience discriminatory processes of gendered Islamophobia, which can result in complex barriers to participation, there is also a political confidence, with many engaging in politics and civic life through a variety of mechanisms. For many, participation is motivated by the understanding that it is a way of countering stereotypes of "Muslim women" and the multiple discriminations they face. Second, we examine how the class backgrounds of the young women influence and play a role in their political participations. We argue that class related factors such as education, social mobility and social capital shape and enable their political participations. Third, we demonstrate how the political geographies of Scotland have worked as a politics of belonging, engendering the participation of many of the young Muslim women in Scottish society.